Simulasi Tegangan pada Rangka Sepeda Motor - Muhammad Hasan Albana; Faizul Praja; Benny Haddli Irawan (Politeknik Negeri Batam, 2015)
The motorcycle frame is important to supported components of the motorcycle and to maintain stability when driving. One of the variables to determine the strength of the frame is to measure the stress when it is loaded. This study was to determine the stress experienced by the frame of the motorcycle when it is given a load of 1960 N and 2450 N in two different types of material, Galvanized Steel and Black Steel (AISI 1080). Research conducted with simulations using software Solidwork 2013. The simulation results indicate that the material Galvanized steel frame permanently deformed when given load 2450 N because the stress (221.6 MPa) is exceed the material's yield strength (203.9 MPa). While the frame of the material Black Steel (AISI 1080) when given a load of 2450 N stress received is 233.9 MPa, still lower than the value of the material's yield strength (375.8 MPa) but displacement that occurs is 21.1 mm.